Improving education in perinatal mental health, a participatory qualitative analysis - Marine Dubreucq; Corinne Dupont; Mathilde Thiollier; Sarah Tebeka; Pierre Fourneret; Marion Leboyer; Sylvie Viaux-Savelon; Catherine Massoubre; Julien Dubreucq (Scientific Reports)
Abstract A recent systematic review found that education programs in perinatal mental health (PMH) had limited effects on detection, referral, and support of parents with perinatal mental health problems. This participative qualitative study (i.e. co-production by academic researchers and researchers with lived experience as equal partners) sought to explore the experiences, views and priorities of persons with lived experience (PWLEs), obstetric providers, childcare health providers and mental health providers (MHPs) on education in PMH. We conducted nine focus groups and 24 individual interviews (n = 84 participants: 24 PWLEs; 30 obstetric providers; 11 childcare health providers and 19 MHPs). We used Braun & Clarke’s inductive six-step process in the thematic analysis. We found some degree of difference in the priorities for education in PMH identified by PWLEs (e.g. person-centred collaborative perinatal healthcare) and providers (e.g. knowledge about perinatal mental health problems). Providers considered PMH assessment as part of their role (except for parents with suicidal ideations or serious mental illness) but reported feeling ill-prepared to do so. Organisational factors comprised PMH integration into standard perinatal healthcare and common culture between non-MHPs and MHPs. Education programs in PMH should be co-designed with PWLEs and focus on providing collaborative person-centred care for all parents.